0.9(z+0.5)=-1.2(z+18)

Simple and best practice solution for 0.9(z+0.5)=-1.2(z+18) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.9(z+0.5)=-1.2(z+18) equation:


Simplifying
0.9(z + 0.5) = -1.2(z + 18)

Reorder the terms:
0.9(0.5 + z) = -1.2(z + 18)
(0.5 * 0.9 + z * 0.9) = -1.2(z + 18)
(0.45 + 0.9z) = -1.2(z + 18)

Reorder the terms:
0.45 + 0.9z = -1.2(18 + z)
0.45 + 0.9z = (18 * -1.2 + z * -1.2)
0.45 + 0.9z = (-21.6 + -1.2z)

Solving
0.45 + 0.9z = -21.6 + -1.2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '1.2z' to each side of the equation.
0.45 + 0.9z + 1.2z = -21.6 + -1.2z + 1.2z

Combine like terms: 0.9z + 1.2z = 2.1z
0.45 + 2.1z = -21.6 + -1.2z + 1.2z

Combine like terms: -1.2z + 1.2z = 0.0
0.45 + 2.1z = -21.6 + 0.0
0.45 + 2.1z = -21.6

Add '-0.45' to each side of the equation.
0.45 + -0.45 + 2.1z = -21.6 + -0.45

Combine like terms: 0.45 + -0.45 = 0.00
0.00 + 2.1z = -21.6 + -0.45
2.1z = -21.6 + -0.45

Combine like terms: -21.6 + -0.45 = -22.05
2.1z = -22.05

Divide each side by '2.1'.
z = -10.5

Simplifying
z = -10.5

See similar equations:

| 2t=32 | | y=15x+250 | | 25.3=w-14.9 | | 3(b-2)=-3 | | 3(n+1)=-15 | | (y^7-y^3)-(y^4-y)= | | y-26=3 | | 40x+18x-3=468 | | x^2-6x+y+5=0 | | 3t+17-4t=-18 | | 2v-1=1 | | -1-2x(1-7)=8 | | -36.8+9.2x= | | 18x+40(x-3)=468 | | 3x(x+10)=99 | | 9=n/13 | | (4x-11)-(-16x-17)= | | 4x^2+25y^2-100y=0 | | 3*(-1)+2*2-3x=-2 | | 3(t-4)=-2(t-3)+14 | | (X-4)(x+12)= | | 2x-21=x+4 | | x^2+17=19 | | 40x-18(x-3)=468 | | y+6.2=9.1 | | 63=c-21+2c | | 3/6=/8 | | 16+x=42 | | 3.29-0.223= | | 4t^2-20t-60=0 | | 2sin(30+x)=3cosx | | 2+p=2 |

Equations solver categories